Development of a high efficiency multi-level inverter - Chong, Justin Wai Mun. (2013)
In order for high efficiency of power drives to be achieved, a non-costly and diode rectifier with electronic switch can be installed to attain unity power factor and low current harmonic distortion. The multi-level inverter is controlled by a synthesis numbers of output voltages level, which results in low voltages harmonic distortion, low voltage stress and high power capability. A single-level inverter is capable of transferring energy with just the flip of a single switch, whereas with a multi-level inverter would require multiple switches, with each switch made up of its own independent structured circuit. The implementation of multiple switches and circuits eventually leads to increment in cost for multi-level Inverters as compared to regular Inverters.